A THEORETICAL STUDY OF ELECTROMAGNETIC TRANSIENTS IN A LARGE PLATE DUE TO VOLTAGE IMPACT EXCITATION - Mukerji, Saurabh Kumar; Singh, Ghanshyam Kumar; Goel, Sandeep Kumar; Manuja, Seema (E M W PUBLISHING, 2008)
Maxwell's equations are solved to determine transient electromagnetic fields inside as well as outside of a large conducting plate of an arbitrary thickness. The plate is carrying a uniformly distributed excitation winding on its surfaces. Transient fields are produced due to sudden application of a d.c. voltage at the terminals of the excitation winding. On the basis of a linear treatment of this initial value problem it is concluded that the transient fields may decay at a faster rate for conducting plates with smaller values of relaxation time. It is also shown that the growth of flux in a perfectly nonconducting plate is a piecewise linear function of time and the current in its excitation winding is a series of step function of time.